Distributed aggregate algorithm for average query based on WSN - LIU Cai-ping1; LI Ren-fa1; LIU Xi-ping2 (Tongxin xuebao)
A distributed aggregate algorithm （DAA） for average query based on WSN was proposed. In DAA, the com- putation process of each node in WSN used the information gathered from just a few nearby neighbors. The algorithm offered a fundamentally distributed solution to analyze data locally without necessarily collected the information of whole nodes to a single central site, and did not require data fusion and long-distance communication. The algorithm could adaptively adjust query range according to query results as well. Analytical and experimental results show that the pro- posed algorithm has the advantages of good scalability、low power consumption, and is able to significantly prolong system life.